Developing Individualized Education Program (IEP) on Early Reading for Special Needs Students in Inclusive Primary Schools in Magetan Regency - N. Asri, Dahlia; E. H. Cahyono, Bambang; P. Trisnani, Rischa (KnE Social Sciences, 2022)
This research describes and explains (i) the condition of early reading for special needs students in inclusive primary schools in Magetan regency, Indonesia; (ii) the teachers’ need for an Individualized Education Program (IEP) for early reading; and (iii) the development of IEP in early reading for special needs students. The study is developmental research introduced by Borg dan Gall. The research was planned to be conducted in four steps: exploration, model development, model testing, and dissemination. However, the current study explains the development of IEP at the exploration step. A descriptive qualitative method was used in the exploration step. Data were collected through document study, observation, and interview, and analyzed using the interactive model. The research at the exploration step showed the following results: First, teachers faced many constraints while teaching early reading to special needs students; each special needs student faced a different obstacle which only a few teachers understood and tackled well. In addition, some obstacles also came from parents who are unaware of their children’s needs and cannot contribute to their studies. Second, teachers need IEP in early reading for special needs students to tackle the different obstacles. Based on the research results, a prototype for IEP in early reading for special needs students at inclusive primary schools in Magetan Regency was designed at the development step. Keywords: Individualized Education Program (IEP), early reading, special need students, inclusive primary school